A community-centric multi-disciplinary education program with the 8-section brocade Tai Chi therapy for patients with osteoarthritis of the knee - a pilot study - Kevin Ki-Wai Ho; Gerald Pong; Queena Wai-Chin Poon; Jojo Yan-Yan Kwok; Wai-Wang Chau; Michael Tim-Yun Ong (BMC, 2021)
Abstract Background Osteoarthritis (OA) of the knee is one of the most common chronic degenerative joint diseases, and a multi-disciplinary approach to educating patients with OA knee are effective in symptoms management. Tai Chi exercise is a novel approach to relieving knee OA symptoms. Combining both educational program and Tai Chi has not yet been explored. Methods Multi-disciplinary education program included a total of 4-week 2-h weekly talks delivered by different health professionals with live demonstrations. This was then followed by a 1-h Tai Chi class (Baduanjin). Results from IPAQ (Physical activity level), WOMAC (evaluate knee OA conditions), and SF-36v2 (quality of life) were collected at the first class of education program, 3 and 6 months after the end of Tai Chi class. CSQ-8 (program effectiveness) was administered on the last day of Tai Chi class. Results One hundred and twelve patients joined the program. The overall attendance was over 90% with close-to-zero dropout rate. Satisfaction scored high in 85% of patients. WOMAC pain scores (p = 0.04) and SF-36v2 emotional role (p = 0.02) were statistically decreasing (improving) at 6 months after the program. SF-36v2 physical role and mental health tended to improve with time. Conclusions Combining both multidisciplinary education program program and Tai Chi exercise for knee OA patients was proven feasible. This program received high satisfaction, high attendance and very low dropout rates without any adverse event. Patients' pain and emotion were significantly improved. A large-scale randomized trial introducing a control group is recommended. Trial registration Registry: ClinicalTrials.gov Registration number: NCT04204213 Date of registration: 18/12/2019 (Retrospectively registered)